Determining the corporate image of Islamic Banks - Pg Morshide, Dk Intan Saidatul Farahin; Wan Jusoh, Wan Jamaliah (Management Research Center, Faculty of Economics and Business, Universitas Indonesia, 2016)
The Islamic banking system is fast growing and gaining global customers’ acceptance. This has led many conventional banks to set up branches which operate in accordance to the Shari’ah principles. The Islamic banking system is expected to face strong competition not only from the Islamic banks but also from well-established conventional banks offering Islamic products and services. Therefore, this research aims to determine customers’ perception towards the corporate image of Islamic banks in a dual banking environment. Corporate identity, reputation, services offered, physical environment, contact personnel, and Shari’ah compliance were hypothesized to influence the corporate image of Islamic banks. A self-administrated questionnaire was distributed to 235 customers of Islamic banks around Kota Kinabalu, Sabah by way of a purposive sampling. Findings indicated a positive overall perception towards corporate image of the Islamic banks with corporate identity ,reputation and contact personnel having significant and positive relationship with corporate image.